1993
DOI: 10.1128/iai.61.6.2357-2368.1993
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for possible involvement of an elastolytic serine protease in aspergillosis

Abstract: A number of isolates ofAspergdilusfumigatus obtained from the hospital environment produced extracellular elastolytic activity. This activity was found to be catalyzed by a single 33-kDa protein which was purified and characterized to be a serine protease. A. fumigatus, when grown on the insoluble structural material obtained from murine and bovine lung, produced the same extracellular 33-kDa elastolytic protease, indicating that this enzyme is likely to be produced when the organism infects the lung. Polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(82 citation statements)
references
References 39 publications
(32 reference statements)
7
73
1
Order By: Relevance
“…The proteinase might also have effect on IgE synthesis by exerting its proteolytic effect on regulatory molecules as observed for the major house dust mite allergen Der p 1 [22]. In addition, extracellular proteases have been considered to play a role in the pathogenesis of aspergillosis [20,21,23,24]. MoAbs against serine proteinases obtained in the present study may also be useful in the study of proteases as major allergens and as virulence factors of pathogenic Aspergilli.…”
Section: Discussionmentioning
confidence: 66%
“…The proteinase might also have effect on IgE synthesis by exerting its proteolytic effect on regulatory molecules as observed for the major house dust mite allergen Der p 1 [22]. In addition, extracellular proteases have been considered to play a role in the pathogenesis of aspergillosis [20,21,23,24]. MoAbs against serine proteinases obtained in the present study may also be useful in the study of proteases as major allergens and as virulence factors of pathogenic Aspergilli.…”
Section: Discussionmentioning
confidence: 66%
“…As has been found in other microorganisms (Table 2), proteases appear to be important pathogenicity factors for Aspergillus species. A 33-kDa subtilisin-like serine protease from Aspergillus flavus and Aspergillus fumigatus that shows cross-reactivity with an IgG antibody displayed proteolytic activity when tested on lung polymers (Kolattukudy et al, 1993;St Leger et al, 1993). Nitrosoguanidine mutants of the gene encoding the 33-kDa protease were significantly less able than the wild type to kill mice, although the mutagenization method used can also generate undetectable secondary mutations explaining the differential virulence levels (Kolattukudy et al, 2000).…”
Section: Pathogenic Species Of the Genus Alternariamentioning
confidence: 99%
“…The nucleotide sequences of 1.2 kb fragments am-pli¢ed from the NSW3 and QLD1 alkaline protease genes were determined. These sequences, which contain the region coding for amino acids 62^402 in the 403 amino acid pre-pro-enzyme, were compared with three partial and complete sequences obtained from human isolates of A. fumigatus which have been reported [20,11,14]. The results showed that the se- quence of the QLD1 fragment was nearly identical to the sequences of the three human isolates whereas the sequence from NSW3 di¡ered signi¢cantly (Table 1).…”
Section: Dna Sequence Analysis Of Nsw3 and Qld1mentioning
confidence: 98%
“…2. Comparison of the deduced amino acid sequences of the alkaline protease from the QLD1, NSW3 and FRR 1266 isolates with Aspergillus fumigatus (AFUM, [14]), Aspergillus nidulans (ANID, [13]) and Aspergillus oryzae (AORY, [4]). Amino acids that are identical to amino acids 62^402 of the AFUM protease are indicated by a dash.…”
Section: Rflp Analysismentioning
confidence: 99%